Communication Challenges of AEC English Teachers in Australia (A case study of the culture shock experienced by AEC teachers in Australia) - Sri Seti Indriani; Ditha Prasanti (West Science Social and Humanities Studies, 2023)
AEC teachers are those who have taught English in a school called Armidale English College. They also have been exposed enough with English language and its culture. AEC has a program of sending its teachers to Australia with a mission to improve their English skills and to gain cultural studies for three months. These English teachers were expected to have a high ability to communicate well in English, they were also expected to be prepared in cultural differences, in fact, what they experienced was far from the expectations for most people. They actually experienced culture shock in Australia. The purpose of this study is to acknowledge the communication challanges and how they experienced the culture shock in Australia. This study was conducted through a qualitative research using case study approach. Data collection techniques consisted of in-depth interviews and documentation studies. The results of the research on the communication challenges by AEC teachers mostly came from themselves and the language which consisted of 1) the accent 2) slang words, 3) vocabularies, and 4) conversation topics. The culture shock they experienced consisted of 1) different mindset 2) openness 3) use of profanity words and 4) life habits. The results also emphasized that overcoming cultural shock does not only focus on having language skills, but also having cultural competence and intelligence.